Financial Performance of BLU Hospital Cluster Before and During the Covid-19 Pandemic - Rasyid , Yuniar Yanuar; Amrullah, Muchamad; Santoso , Kurniawan; Putra , Syahri Azda (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2024)
BLU Hospital received government assistance for operational costs in handling Covid-19 patients. The purpose of this study is to analyze government assistance for operational costs in handling Covid-19 patients, the type of BLU Hospital, and the number of patients on the maturity level of financial aspects, and to compare the maturity level of financial aspects before and during the government's assignment in handling the Covid-19 pandemic. This study uses inferential statistics. The data used is secondary data. The analysis method is quantitative data analysis using multiple regression methods and mean difference test methods. The sample size is a saturated sample from the population of BLU Hospitals. The results of the study show no significant difference between those who did not receive assistance and those who received assistance on the Cash Optimization Ratio and Current Ratio. There is a significant difference between those who did not receive assistance and those who received assistance on POBO, Return on Assets, Return on Equity, and Total Independence.